Buried too deep - Rose, Karen, 1964- (Rose, Karen, 1964- New Orleans novels, 2024)
"Three can keep a secret if two of them are dead. Working as the nighttime security guard of Broussard Private Investigations, Phineas Bishop has been working through overwhelming PTSD episodes from his Army service while still utilizing his military skills. But when a violent break-in occurs at the office, the accusatory eyes of his team glance to Phin, and he resolves to track down the intruder and earn back the trust of his team. Phin's only lead and witness is Cora Winslow, a spirited librarian who also needs answers. Her father's body has been discovered under a recently demolished building, murdered twenty-three years ago. So, who has been sending her the handwritten letters every year since he abandoned Cora's family when she was five, and who is after her now? Clearly, someone wants to keep Cora in the dark. And now, they're coming for her. As Cora's bodyguard, Phin is surprised by his fondness for the woman's fierce determination and research prowess. But New Orleans's Garden District holds secrets as old as the streets themselves. With help from the entire Broussard P.I. team, Phin and Cora enter a labyrinth of fraud, trafficking, and homicide that threatens to bury them all."--